VALIDITAS BUKU AJAR MATEMATIKA DASAR TERINTEGRASI PENDIDIKAN KARAKTER - Martyana Prihaswati; Eko Andy Purnomo; Sukestiyarno Sukestiyarno; Mulyono Mulyono (Universitas Muhammadiyah Semarang, 2018)
The establishment of a healthy ecosystem in the industrial revolution era 4.0 begins with the formation of millennial characters who are currently experiencing degradation. The tendency of basic mathematics learning that gives more attention to the cognitive aspects has an impact on the mindset that is formed, which is learning to get value, not learning to form characters that are ready to face the industrial era 4.0. The need to link learning with character values can be realized in the development of an integrated mathematics textbook of character education. The purpose of this study was to determine the validity of integrated basic textbooks in character education. The research method used is research and development methods or Research and Development (R & D) with procedures in accordance with the development model of Borg & Gall. The results of the research shown in the design validation resulting in an average score of 3.13 including the valid criteria. So that the basic mathematics textbooks are integrated valid character education. Further research is needed in the trial class as the implementation of integrated basic textbooks on character education.Keywords : Borg & Gall, textbooks, character education